A176 SOFOSBUVIR/VELPATASVIR-BASED REGIMENS ARE ASSOCIATED WITH EXCELLENT EFFICACY AND A SIGNIFICANT IMPROVEMENT OF PATIENTS-REPORTED OUTCOMES ACROSS PATIENT POPULATIONS: FROM NON-CIRRHOTICS TO COMPENSATED CIRRHOTICS TO DECOMPENSATED CIRRHOTICS. (1st March 2018) - Younossi, Z M; Stepanova, M; Feld, J; Zeuzem, S; Sulkowski, M S; Foster, G R; Mangia, A; Charlton, M; O'Leary, J; Curry, M; Nader, F; Henry, L; et al.
Abstract: Aims: Our aim was to assess the impact SOF/VEL±ribavirin (RBV) on patient-reported outcomes (PROs) in HCV patients with and without decompensated cirrhosis. Methods: Four PRO questionnaires (SF-36, CLDQ-HCV, FACIT-F, WPAI:HCV) were collected in 4 phase 3 trials of SOF/VEL (ASTRAL-1, 2, 3 and 4). The baseline PROs and treatment-emergent changes in PROs were compared among 3 groups (no cirrhosis, compensated cirrhosis, decompensated cirrhosis) while receiving +/- RBV-containing regimens. Results: 1, 701 patients received SOF/VEL or SOF/VEL+RBV or SOF+RBV for 12 or 24 weeks: 1, 112 without cirrhosis, 338 with compensated cirrhosis, 251 with decomp cirrhosis; 488 received RBV-containing regimens [SOF+RBV (N=401) and SOF/VEL+RBV (N=87)] and 1, 213 received RBV-free SOF/VEL. Decomp cirrhotics were older, more commonly male and less treatment-naive, and had more pre-treatment depression, anxiety, type 2 diabetes, fatigue and insomnia (all p<0.002). SVR-12 was 84.7% (SOF/VEL in decomp cirrhosis, all GTs), 98.5% (SOF/VEL non-cirrhotics, all GTs), 66.3% (SOF+RBV in GT3 cirrhotics), 94.7% (SOF+RBV in non-GT3 cirrhotics) and 94.3% (SOF/VEL+RBV in decomp cirrhotics, all GTs). Cirrhotic patients had significantly lower baseline PRO scores (up to -33.5 points on a universal 0–100 PRO scale in patients with decomp cirrhosis in comparison to patients without cirrhosis; p<0.05 for all but three PRO domains). By the end of treatment with RBV+ regimens, changes in PROs were similar across 3 groups (all p>0.01) and included moderate improvements in some PROs (up to +11.8, p<0.05 for 8/26 PRO scores) and moderate decrements in others (up to -7.1, p<0.05 for 6 mental health-related PRO scores). After treatment cessation, improvements from baseline (up to +12.6 points by post-treatment week 4, up to +14.2 by week 12, +17.1 by week 24) were again similar in all patients regardless of cirrhosis status (all p>0.01). By SVR-12 follow-up, PRO improvements were sustained in patients with decompensated cirrhosis: average across PROs +5.8 vs. +4.1 in compensated cirrhosis or no cirrhosis, p<0.05 for 7/26 PROs. In multivariate analysis, compensated cirrhosis was associated with additional +2.3 to +5.0 points improvement of treatment-emergent PRO (all p<0.05), decompensated cirrhosis – with +5.5 to 9.1 points (all p<0.002) in SOF/VEL regimen. Conclusions: HCV patients with decompensated cirrhosis experience the greatest improvement of their PRO scores during treatment with SOF/VEL regimen. SVR is associated with significant improvements in PROs, especially in patients with decompensated cirrhosis. Funding Agencies: Gilead Sciences, Inc.